2021
DOI: 10.1002/iid3.507
|View full text |Cite
|
Sign up to set email alerts
|

Impaired T helper cell responses in human immunodeficiency virus‐exposed uninfected newborns

Abstract: Introduction: HIV-exposed uninfected (HEU) newborns suffer from higher risks of opportunistic infections during the first months of life compared to HIV-unexposed uninfected (HUU) newborns. Alterations in thymic mass, amounts of T helper (Th) cells, T-cell receptor diversity, and activation markers have been found in HEU newborns, suggesting alterations in T cell ontogeny and differentiation. However, little is known about the ability of these cells to produce specialized Th responses from CD4 + T cells. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Both CD4 + and CD8 + T cell compartments in iHEU had lower frequencies of activated cells and memory differentiated cells expressing either PD-1 and/or perforin compared to iHUU. Although studies conducted before the wide adoption of perinatal ARV treatment reported heightened immune activation and/or exhaustion in iHEU 48 , 49 , more recent studies have shown reduced or impaired memory T cells among iHEU compared to iHUU 17 , 50 52 . Such T cell alterations were associated with poor responses to vaccines and/or increased hospitalisation 50 , 51 .…”
Section: Discussionmentioning
confidence: 94%
“…Both CD4 + and CD8 + T cell compartments in iHEU had lower frequencies of activated cells and memory differentiated cells expressing either PD-1 and/or perforin compared to iHUU. Although studies conducted before the wide adoption of perinatal ARV treatment reported heightened immune activation and/or exhaustion in iHEU 48 , 49 , more recent studies have shown reduced or impaired memory T cells among iHEU compared to iHUU 17 , 50 52 . Such T cell alterations were associated with poor responses to vaccines and/or increased hospitalisation 50 , 51 .…”
Section: Discussionmentioning
confidence: 94%
“…We reported a decrease in the proportion of differentiated cells, both effector and suppressor cells. Interestingly, many of the T lymphocytes found are in undifferentiated stages (known as Th0), in which their activation by antigen-presenting cells did not complete 19 . This suggests that even though DCs are specifically characterized for maturing adaptive responses, despite being increased with higher levels of CD80 and CD86, they are not efficient in activating and maturing T cell responses.…”
Section: T Lymphocytesmentioning
confidence: 99%
“…The aberrant adaptive immune responses observed in CHEU may originate from alterations in T-cell ontogeny and differentiation [ 58 ]. Thymopoiesis, the process whereby T-cells mature and differentiate, takes place in the thymus.…”
Section: Altered Adaptive Immune Responses Due To Peripartum Hiv And/...mentioning
confidence: 99%
“…The CHEU group had smaller subsets of Th 1 , Th 2 , Th 17 , and CD4+ CD25 + + (presumably Treg) T-cells compared to their unexposed counterparts. The reduced proportions of these Th cells found in CHEU resulted in impaired effector cytokine production [ 58 ].…”
Section: Altered Adaptive Immune Responses Due To Peripartum Hiv And/...mentioning
confidence: 99%
See 1 more Smart Citation